Program artystyczny Teatru Rapsodycznego - Popiel, Jacek (Wydawnictwo Naukowe UAM, 2004)
The history of the Rhapsody Theatre is one of the most dramatic chapters in the history of the 20th century Polish theatre. The group established in Cracow in 1941, managed by Mieczysław Kotlarczyk, was operating during the Nazi occupation as a clandestine theatre. In the first years after the end of World War II it played a significant role, realising the dreams of its founders from the time of Nazi occupation concerning the repertory programme of the theatre, in which the main place would be that of Polish Romantic and neo-Romantic writers. In 1953 the Rhapsody Theatre was closed for propagation of the „mistaken, antirealistic and mystic, ideologically hostile" artistic programme. It was reopened in 1957 on the wave of the post-October political thaw, but was finally liquidated by the authorities of the Polish People's Republic in 1967. In the article the author discussed the fundamental assumptions of the artistic programme of the Rhapsody Theatre (sources of inspiration, similarities to the idea of the national theatre, theatre of the word as a theatre of imagination, the art of acting, rules of recitation).
Artistic programme of Rhapsody Theatre